PENGUJIAN SAH TIDAKNYA PENGHENTIAN PENYIDIKAN MELALUI LEMBAGA PRAPERADILAN - Bernadetta Rumondang F S (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract This journal writing is aim to analyze and study wether halting command letter for quest is the only one prequirement to submit test about legal or not investigation halting through pretrial investigation and to analyze and assess the new formulation of the Termination of the Investigation within the KUHAPidana (book of judicial procedure of Criminal Law) in the future. This journal is compiled using normative, juridical research method with respect to its approach to legislation, concept and case so that based upon the result of this Journal, it was demonstrated that Warrant for Termination of Investigation (SP3) is not the sole requirement to file a request that the investigation be evaluated through the Pretrial Institution, whereas the formulation of the Warrant for Termination of Investigation within the renewal of KUHAPidana (book of judicial procedure of Criminal Law) in the future is to reformulate some of the provisions on the definition of Investigation and also to reformulate the time limit of Investigation. This reformulation is intended to provide legal assurance for those who report crimes, crime victims and criminal suspect, which there is no clarity or clear reason while still at the level of the Indonesian National Police Investigation. Key words: investigation halting, pretrial investigation, Warrant for Termination of Investigation (SP3) Abstrak Penulisan jurnal ini bertujuan untuk menganalisis dan mengkaji apakah Surat Perintah Penghentian Penyidikan merupakan satu-satunya syarat untuk mengajukan pengujian tentang sah tidaknya penghentian penyidikan melalui Lembaga Praperadilan serta menganalisis dan mengkaji formulasi penghentian penyidikan bagi pembaharuan KUHAPidana di masa yang akan datang. Jurnal ini disusun menggunakan metode penelitian yuridis normatif dengan pendekatan perundang-undangan, pendekatan konsep dan pendekatan kasus. Berdasarkan hasil penelitian diketahui bahwa Surat Perintah Penghentian Penyidikan (SP3) bukan merupakan satu-satunya syarat untuk mengajukan pengujian tentang sah tidaknya penghentian penyidikan melalui Lembaga Praperadilan, sedangkan formulasi penghentian penyidikan bagi pembaharuan KUHAPidana di masa yang akan datang adalah dengan merumuskan beberapa pasal tentang pengertian penghentian penyidikan, serta batas waktu penyidikan, formulasi ini dimaksudkan untuk memberikan kepastian hukum bagi Pelapor, Korban Tindak Pidana dan Tersangka yang perkara pidananya berlarut-larut tidak ada kejelasannya di tingkat penyidikan. Kata kunci: Penghentian Penyidikan, Lembaga Praperadilan, Surat Perintah Penghentian Penyidikan (SP3)